Analisis Faktor Risiko Pencemaran Mikroba Pada Produk Obat Tradisional (Studi Titik Kendali Kritis dalam Proses Produksi Obat Tradisional Bentuk Serbuk pada Perusahaan Jamu di Kalimantan Selatan). - Safriansyah, Safriansyah; Suhartono, Suhartono; Joko, Tri (Master Program of Environmental Health, Faculty of Public Health, Diponegoro University, 2002)
ABSTRACT Background : Consuming the medicinal herbs has become the habitual legacy in Indonesian community. Powder packed medicinal herbs are enjoyed and commonly used. Some research result and the quality control activity of herbal medicine by legal institution proved that the powder herbs produks are not save from biological hazard yet, as some tixic fungsi are available in the market. Methods : This research used an observation study with the cross-sectional approach to observe the microbial contamination's risk factoring processing the herbal medicine. The samples of researches all the kind of herbal medicine, 13 product in from of powder produced by the herbal company in south Kalimantan in April and May 2002, by the Hazard Analysis Critical Control Point (HACCP) model Approach, this research determined 6 critical procedure, sorting procedure, washing procedure, drying procedure, pre-packaging product storage and primary packaging procedure whereas the microbial contamination level was measured to 3 parameter of microbial number from the end product, which were ALT (total bacteria), MPN Coliform and Kapang-Khamir. Results : Chi-square test’s result in the limited sample (fisher’s Exact Test) and also Rank Spearman correlation coefficient indicated a significant relationship between the implementation level of simplisia drying procedure and primary packaging procedure with the total bacteria contamination level (p < 0,05). Moreover, with the Rang Spearman correlation coefficient test the research found the significant relationship between the implementation level of pre – packaging product storage producer and kapang khamir contamination level (P<0,05). There were no significant relationship between variable in the production process with the Coliform contamination level (MPN Coliform). The result of logistic regression analysis showed the effect between the simplisia storage procedure, sorting and the drying procedure to the total bacteria contamination level (ALT) in the end product. Recommendation : Therefore, to improve the quality of microbiological herbal powder product, especially in minimizing the total bacteria and Kapang-Khamir contamination, it is suggested to conduct some improvement in the implementation of simplisia storage procedure, sorting, drying, pre-packaging product storage and primary packaging. Keywords = medicinal herb, microbial contamination. HACCP